2018
DOI: 10.1016/j.bbamcr.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 controls NRF2 antioxidant activity in prevention of diabetic kidney disease

Abstract: Oxidative stress and P53 contribute to the pathogenesis of diabetic kidney disease (DKD). Nuclear factor erythroid 2-related factor 2 (NRF2) is a master regulator of cellular antioxidant defense system, is negatively regulated by P53 and prevents DKD. Recent findings revealed an important role of mouse double minute 2 (MDM2) in protection against DKD. However, the mechanism remained unclear. We hypothesized that MDM2 enhances NRF2 antioxidant signaling in DKD given that MDM2 is a key negative regulator of P53.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…32,33 Not until recent years was P53 identified to play a pathogenic role in DM and its complications. P53 is highly expressed under diabetic condition, contributing to the pathogenesis of DM, 34,35 diabetic cardiomyopathy, 36 nephropathy 22,37 and peripheral artery disease. 38 Here we report the pathogenic effect of P53 on diabetic aortic endothelial dysfunction, with miR-34a to be the mediator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32,33 Not until recent years was P53 identified to play a pathogenic role in DM and its complications. P53 is highly expressed under diabetic condition, contributing to the pathogenesis of DM, 34,35 diabetic cardiomyopathy, 36 nephropathy 22,37 and peripheral artery disease. 38 Here we report the pathogenic effect of P53 on diabetic aortic endothelial dysfunction, with miR-34a to be the mediator.…”
Section: Discussionmentioning
confidence: 99%
“…To study the effect of P53/miR-34a inhibition on aortic endothelial dysfunction under DM, pifithrin-α (PFT-α, 1.1 mg/kg, intraperitoneally injected three times weekly 21,22 ; MedChem Express, Shanghai, China) or miR-34a-I (2 mg/kg, subcutaneously injected once weekly 23 ; Thermo Fisher, Shanghai, China) was delivered to the diabetic mice immediately after DM was confirmed, for 24 weeks. In order to investigate the role of SIRT1 in mediating miR-34a-I's action, the diabetic mice were treated with EX-527 (2 mg/kg, 24 intraperitoneally injected three times weekly; MedChem Express) in the presence of miR-34a-I, for 24 weeks.…”
Section: Animal Housing and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, multi‐omics studies have shown that MDM2 plays an important role in the glomeruli and tubules of the DN kidneys, as indicated by reductions in the expression of two key metabolite biomarkers, 3‐methylcrotonylglycine and uracil, when mice were treated with nutlin‐3 . Guo et al have observed that MDM2 controls the antioxidant activity of nuclear factor erythroid 2‐related factor 2 in mice with diabetic kidney disease by inhibiting p53.…”
Section: Roles Of Mdm2 In Kidney Diseases and Diabetesmentioning
confidence: 99%